2022
DOI: 10.3389/fnut.2022.800996
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Vegetable-Fruit-Soy Dietary Pattern, a Reference From Mediterranean Diet, Protects Against Postmenopausal Breast Cancer Among Chinese Women

Abstract: BackgroundThe diet-center hypothesis has gained much support from the apparent protective effect of the Mediterranean diet on breast cancer. However, the evidence of the association between Mediterranean diet adherence and breast cancer molecular subtypes remains small, especially in non-Mediterranean populations.MethodsThe subjects from the Chinese Wuxi Exposure and Breast Cancer Study, a population-based case-control study, included 818 patients and 935 healthy controls. A validated food frequency questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Another study in Iran found a significant positive correlation between dietary glycemic index and the incidence rate of BC (26), while high dietary fiber intake, such as beans and grains, was shown to reduce the risk of estrogen receptor negative (ER-) and progesterone receptor negative (PR-) BC in the United States (27). Meat and processed meat diets were associated with a higher risk of BC in a Chinese study (28), while the consumption of vegetables, fruit, and soybeans reduced the risk of postmenopausal BC, especially ER-and ER-/PR-subtypes (9). The consumption of fresh fruit and nuts was negatively correlated with the risk of menopausal BC, and foods with a high sodium content were positively correlated with the risk of menopausal BC in a South African study (29), and a multigrain diet reduced the risk of BC in a South Korean study (30).…”
Section: Dietary Patterns and The Risk Of Bcmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study in Iran found a significant positive correlation between dietary glycemic index and the incidence rate of BC (26), while high dietary fiber intake, such as beans and grains, was shown to reduce the risk of estrogen receptor negative (ER-) and progesterone receptor negative (PR-) BC in the United States (27). Meat and processed meat diets were associated with a higher risk of BC in a Chinese study (28), while the consumption of vegetables, fruit, and soybeans reduced the risk of postmenopausal BC, especially ER-and ER-/PR-subtypes (9). The consumption of fresh fruit and nuts was negatively correlated with the risk of menopausal BC, and foods with a high sodium content were positively correlated with the risk of menopausal BC in a South African study (29), and a multigrain diet reduced the risk of BC in a South Korean study (30).…”
Section: Dietary Patterns and The Risk Of Bcmentioning
confidence: 99%
“…A Mediterranean-style diet has been shown to reduce the risk of BC (9), while a low-fat diet reduced mortality in post-menopausal patients (10), and healthy eating patterns improved the quality of life of patients with BC (11). However, the role of dietary patterns in populations with specific BCs is inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…After the layers of screening, a total of 52 studies (35 articles were case-control studies [11][12][13][14][15][16]18,38,39,[41][42][43][44][45][46][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75]] and 17 articles were cohort studies [17,19,20,[34][35][36][37]40,47,[76][77][78][79][80][81][82][83]) we...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Furthermore, the meta-regression analysis results showed a statistical difference between China and Japan (p-difference = 0.022). Twenty-five studies [15,16,[18][19][20][35][36][37][39][40][41]60,61,[72][73][74]80,83] were included in the dose-response analysis for total soy product consumption and risk of cancer, and there was a nonlinear relationship between them (p-nonlinear = 0.0028) (Figure 3A,B). When an additional 54 g of total soy product was consumed daily, the cancer risk began to decline (RR: 0.89; 95% CI: 0.79, 0.99).…”
Section: Total Soy Product Consumption and Cancer Riskmentioning
confidence: 99%
“…A dietary pattern rich in fruits, soy, and vegetables was associated with a reduced risk of postmenopausal breast cancer in Chinese women, particularly in those with ERsubtypes [101]. This Mediterranean-style diet, observed in an Asian population, is defined by the consumption of plentiful plant-based foods, which is a fundamental component of the traditional Mediterranean diet known for its potential anticancer, anti-inflammatory, and antioxidant effects [102].…”
Section: Fruits Vegetables and Plant-based Foodsmentioning
confidence: 99%